2021
DOI: 10.1016/j.ajog.2020.12.1212
|View full text |Cite
|
Sign up to set email alerts
|

Predicting cesarean delivery for failure to progress as an outcome of labor induction in term singleton pregnancy

Abstract: BACKGROUND: Induction of labor is one of the most common interventions in modern obstetrics, and its frequency is expected to continue to increase. There is inconsistency as to how failed induction of labor is defined; however, the majority of studies define success as the achievement of vaginal delivery. Induction of labor in nulliparous women poses an additional challenge with a 15% to 20% incidence of failure, ending in emergency operative deliveries. The Bishop score has been traditionally used before deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 65 publications
1
27
0
3
Order By: Relevance
“…Much of the literature surrounding failed induction of labor use different or poorly defined endpoints such as failure to delivery vaginally, not achieving vaginal delivery within 24 hrs, or not entering the active phase of labor. However, our work now justifies to design studies in larger cohorts with the aim of identifying predictive immune markers of failed induction of labor prior to commencement of active labor (9,(45)(46)(47)(48). Potential future clinical studies should also include parallel analyses of choriodecidual material to help understand local immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the literature surrounding failed induction of labor use different or poorly defined endpoints such as failure to delivery vaginally, not achieving vaginal delivery within 24 hrs, or not entering the active phase of labor. However, our work now justifies to design studies in larger cohorts with the aim of identifying predictive immune markers of failed induction of labor prior to commencement of active labor (9,(45)(46)(47)(48). Potential future clinical studies should also include parallel analyses of choriodecidual material to help understand local immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the time interval between labor induction, the establishment of latent labor (defined as regular contractions leading to cervical changes from 0 to 6 cm) and the onset of active labor (defined as cervical dilatation ≥ 6 cm with regular uterine contractions ≤ 3 min apart) remains unpredictable. Similarly, induction complications associated with failure of successful labor initiation, prolonged labor progression, subsequent labor arrest, development of chorioamnionitis or failed induction resulting in cesarean delivery (7)(8)(9), are difficult to predict. Prolonged labor is associated with severe complications and morbidity for the mother and her offspring, most importantly chorioamnionitis, uterine atony and postpartum hemorrhage (4).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that the fetal occiput and spine position determination by ultrasound, preinduction, do not correlate with the mode of birth while others concluded that fetal head position is, indeed, a significant predictor. 52,[59][60][61] Identifying the fetal spine and occiput position by ultrasound is done transabdominally. The curvilinear transducer is applied to the maternal abdomen to get an axial view of the fetal abdomen to visualize the fetal spine location then the transducer is slid down the maternal abdomen systematically to reach the fetal head.…”
Section: Assessment Of Fetal Head Position and Stationmentioning
confidence: 99%
“…The determination of fetal head station by measuring the angle of progression (AoP) was found to be a significant independent predictor for the success of induction of labor and particularly when associated with nulliparity. 61,65,66 Angle of progression (Figure 5) is the angle between the sagittal midline of the symphysis pubis and line dropping from the lowermost point of the symphysis pubis tangentially to the deepest point of the fetal head, on transperineal ultrasound. 67 The automated assessment of AoP, now available in some ultrasound systems, measures the AoP in a parasagittal plane and was demonstrated to be feasible, correlate well with assessment of fetal station by vaginal examination 68 and in excellent agreement with the originally described midsagittal AoP 69 .…”
Section: Assessment Of Fetal Head Position and Stationmentioning
confidence: 99%
See 1 more Smart Citation